Novel Mutation in Spectrin-like Repeat 1 of Dystrophin Central Domain Causes Protein Misfolding and Mild Becker Muscular Dystrophy - Acsadi, Gyula (American Society for Biochemistry and Molecular Biology, 2012)
Mutations in the dystrophin gene without disruption of the reading frame often lead to Becker muscular dystrophy, but a genotype/phenotype correlation is difficult to establish. Amino acid substitutions may disrupt binding capacities of dystrophin and have a major impact on the functionality of this protein. We have identified two brothers (ages 8 and 10 years) with very mild proximal weakness, recurrent abdominal pain, and moderately elevated serum creatine kinase levels. Gene sequencing revealed a novel mutation in exon 11 of the dystrophin gene (c.1280T>C) leading to a L427P amino acid substitution in repeat 1 of the central rod domain. Immunostaining of skeletal muscle showed weak staining of the dystrophin region encoded by exons 7 and 8 corresponding to the end of the actin-binding domain 1 and the N-terminal part of hinge 1. Spectrofluorescence and circular dichroism analysis of the domain repeat 1-2 (R1-2) revealed partial misfolding of the L427P mutated protein as well as a reduced refolding rate after denaturation. Based on computational homology models of the wild-type and mutated R1-2, a molecular dynamics study showed an alteration in the flexibility of the structure, which also strongly affects the conformational space available in the N-terminal region of the fragment. Our results suggest that this missense mutation hinders the dynamic properties of the entire N-terminal region of dystrophin.